2020
DOI: 10.20473/jn.v14i3.17046
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the CIPP evaluation model in Indonesian nursing schools

Abstract: Introduction: The implementation of the Indonesian National Nursing Competency Test (INNCT) has faced several challenges, especially related to the low pass rate. The pass rate has decreased over time, but the number of examinees has increased. The aim of this study was to evaluate the nursing schools’ performance in INNCT using the Context Input Process Product (CIPP) evaluation model.Methods: A quantitative description was used in this study. The Performance Evaluation of Nursing Program Questionnaire based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
(11 reference statements)
0
7
0
4
Order By: Relevance
“…The example of exit exam set by the American Board of Cardiovascular Perfusion are basic science and clinical science exams as many employers and some state licensure applications requirement (Riley et al, 2006). This is also supported by previous study conducted among nurses in Indonesian nursing institutions where the quality of a nursing education program is evidenced by the performance of its graduates on the licensure examination, hence exit exam is needed (Siswadi, 2019). Therefore, the exit exam is crucial to determine students' progress from didactic to the clinical phase and every student must pass the competency exit exam to obtain entry to the clinical employment (Riley et al, 2006).…”
Section: Processmentioning
confidence: 69%
See 1 more Smart Citation
“…The example of exit exam set by the American Board of Cardiovascular Perfusion are basic science and clinical science exams as many employers and some state licensure applications requirement (Riley et al, 2006). This is also supported by previous study conducted among nurses in Indonesian nursing institutions where the quality of a nursing education program is evidenced by the performance of its graduates on the licensure examination, hence exit exam is needed (Siswadi, 2019). Therefore, the exit exam is crucial to determine students' progress from didactic to the clinical phase and every student must pass the competency exit exam to obtain entry to the clinical employment (Riley et al, 2006).…”
Section: Processmentioning
confidence: 69%
“…As emphasized by the American Academy of Cardiovascular Perfusion, one of the qualities for an effective Perfusion Education Program is the requirement of institution and syllabus to be structured and certified and provide skilled instructors to continue education in improving knowledge and skill. The importance of having similar and comprehensive syllabus is also supported by previous study conducted in Indonesia among nurses revealed that there were disparity of nurses passing rate at 56.5% due to unstandardized syllabus (Siswadi et al, 2019). These can be due to the variety of learning and in the education standard for every nursing programme.…”
Section: Inputmentioning
confidence: 77%
“…On this occasion, the evaluation was focused on five aspects, namely: context (context), preparation (input), process (process), outcome (product), and impact (impact). According to Siswadi et al (2019), this evaluation model framework is more comprehensive to guide planning, implementation, and assessment, especially in learning programs. This evaluation research was conducted from April to May 2020.…”
Section: Methodsmentioning
confidence: 99%
“…This study shows the novelty of the review of the accreditation model with 9 criteria, the majority of which previous research only used 7 criteria carried out at one of the universities in Java, namely Bina Bangsa University, which had not previously been accredited by BAN-PT. Previous studies assessed the quality and benefits of higher education programs (Lopez et al, 2011;Lippe & Carter, 2018;Finney, 2019;Siswadi, Houghty, & Agustina, 2020). However, these studies were not carried out at universities that have not been accredited as in this study.…”
Section: Introductionmentioning
confidence: 98%